Students and lecturers' perspectives of causes’ and management of deviant behaviours among University Students in Kwara State, Nigeria - Akinnubi, O. P.; Alabi, A. T.; Oladimeji, R. M. (African Perspectives of Research in Teaching & Learning, 2021)
This study is a report on causes and management of deviant behaviours among students in universities in Kwara State, Nigeria. The research design for this study was a descriptive survey. Thirty lecturers and 150 final year students were selected as participants in the study. An instrument validated was used to elicit relevant information from the participants. Descriptive statistics of frequency, percentage, rank ordering and mean were used to answer the research questions raised in the study. The findings of the study showed that examination malpractice was ranked the most prevalent deviant behaviour among students in the universities. The major cause of deviant behaviours was peer influence. It was agreed that there were strategies put in place by the university management to curb deviant behaviours among the students. It was recommended that parents should inculcate right moral/religious values in their children while at home. Also, the university authority should ensure that all activities relating to examinations are handled with a high sense of responsibility by those concerned, and educate students on sex education so that they would not fall victims of health risks such as HIV/AIDs. Keywords: Deviant behaviours, Causes, Management, University students
Article published in the African Perspectives of Research in Teaching & Learning (APORTAL) Vol 5(1): 2021
Keywords: Deviant behaviours; Causes; Management; University students; Deviant behavior; Students assistance programme